Crystalline iron oxide nanotube arrays with high aspect ratio as binder free anode for Li‐ion batteries. Issue 8 (11th March 2014) - Pervez, Syed Atif; Kim, Doohun; Farooq, Umer; Yaqub, Adnan; Choi, Jeong‐Hee; Lee, You‐Jin; Muhammad, Shoaib; Doh, Chil‐Hoon
<x xml:space="preserve">Abstract</x> A comprehensive electrochemical study of crystalline iron oxide nanotube arrays grown in a highly ordered form with a high aspect ratio is presented. Nanotube arrays, thickness of ∼5 µm and tube diameter ∼100 nm, were synthesized through an optimized two‐step anodization technique. The morphology and the chemical composition of the resulting materials were characterized by field‐emission scanning electron microscopy, X‐ray diffraction, Rietveld analysis and Raman spectroscopy. The electrochemical response was evaluated by cyclic voltammetry, galvanostatic charge/discharge cycling, and electrochemical impedance spectroscopy on cells with Li metal as the counter and reference electrodes. The results have shown an excellent electrochemical response in terms of charge/discharge capacity (2775 µAhcm−2 at 100 µAcm−2) and rate capability (150 µAhcm−2 at 800 µAcm−2). Cyclic performance was also exceptional as a high reversible capacity (350 µAhcm−2 at 200 µA cm−2) was retained for 100 charge/discharge cycles. Such an enhanced electrochemical response is attributed to the unidirectional morphology of the nanotubes with high aspect ratio, favoring fast Li+ ion diffusion and improved electron transport. Also, avoiding use of binder and conductive carbon agents contribute towards high energy density of the anode material.